PSYCHOLOGICAL FIRST AID TO REDUCE TRAUMA AND DEPRESSION IN THE VICTIMS OF SEXUAL ABUSE: LITERATURE REVIEW - Rosyida, Naila Zulfa; Sari, Jayanti Dian Eka; Fatah, Mohammad Zainal (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: The most concerning now is the increasing cases of sexual abuse. The impact of sexual abuse is very detrimental, victims will experience a decrease in appetite, stress, trauma, and even depression. Purpose: To find out the description of Psychological First Aid (PFA) for victims of sexual abuse. Method: This is narrative literature review. The inclusion criteria used were the year of publication between 2019-2023, free full text, English or Indonesian, research subjects were victims of sexual abuse, victims' families, and psychology. The data searching method used was the Boolean searching method with the keywords